Diffuse-type Gastric Cancer - Jie-Hyun Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2022)
Gastric cancer is the most prevalent malignant tumor in Korea. Histologically, it is often classified into intestinal-type and diffuse-type. Intestinal-type gastric cancer is known to occur mainly from chronic gastritis caused by Helicobacter pylori (H. pylori) through atrophic gastritis and intestinal metaplasia, a precancerous change of the mucosa, whereas diffuse-type gastric cancer is caused by H. pylori infection, wherein active inflammation of the gastric mucosa occurs without precancerous changes in the mucosa. Compared with intestinal-type gastric cancer, it occurs at a young age, there is no difference in male to female ratio, or tends to occur more in women, and is more aggressive than intestinal-type gastric cancer. Intestinal-type gastric cancer is predominant in East Asian populations such as Koreans and Japanese, whereas diffuse-type gastric cancer has more uniform geographic distribution. In the present manuscript, I have reviewed diffuse-type gastric cancer, distinct from intestinal-type gastric cancer.